Learn PowerShell scripting in a month of lunches - Jones, Don 1971-; Hicks, Jeffery (Manning Publications, 2018)
Discover how scripting is different from command-line PowerShell, as you explore concrete hands-on examples in this handy guide. --
Includes bibliographical references and index. - Online resource; title from title page (Safari, viewed August 13, 2018)
Keywords: Microsoft Windows (Computer file); Windows PowerShell (Computer program language); Application software -- Development; Windows PowerShell (Langage de programmation); Logiciels d'application; Développement; Application software; Development